MiR-128-3p mediates MRP2 internalization in estrogen-induced cholestasis through targeting PDZK1 - Yue Zu; Qianyan Gao; Yisheng He; Qiao Deng; Guodong Li; Xiping Li; Tianze Shang; Xinwei Cheng; Chenglong Zhu; Jianqiao Wang; Dong Liu; Chengliang Zhang (Acta Materia Medica)
Estrogens have been reported to cause dysfunction in biliary transport systems, thereby inducing cholestasis. Multidrug resistance-associated protein 2 (MRP2) is a transporter responsible for independent bile flow. Emerging evidence indicates that PDZ domain containing 1 (PDZK1) regulates localization of MRP2; however, PDZK1’s role and regulatory machinery in MRP2-mediated estrogen-induced cholestasis (EIC) remain unclear. Herein, in a mouse model of EIC, we observed downregulated PDZK1 expression in the liver and enhanced intracellular domain MRP2 internalization. Notably, expression of miR-128-3p, a potential biomarker of estrogen-related cholestasis discovered by our group, was significantly elevated. We demonstrated that miR-128-3p targeted the 3’-untranslated region of PDZK1 in EIC and consequently promoted MRP2 internalization. Accordingly, miR-128-3p suppression upregulated PDZK1, thereby suppressing MRP2 internalization and significantly attenuating cholestatic liver disease. Furthermore, we observed MRP2 internalization and PDZK1 downregulation, as well as excessive miR-128-3p, in clinical samples from patients with cholestatic liver injury. Overall, our findings illustrate that miR-128-3p inhibits PDZK1 expression, thereby inhibiting the membrane localization of MRP2 in EIC. Enhancing or restoring PDZK1 expression might therefore have therapeutic potential for cholestatic liver injury.